Peran Gamifikasi E-Commerce Untuk Mendukung Ekonomi Kreatif - Qurotul Aini; Mukti Budiarto; Aulia Edliyanti (IJAcc, 2021)
In accordance with Presidential Decree Number 142 of 2018 on Economic Development Master Plan 2018-2025 National Creative that serve as the foundation in developing a creative economy that supports the national policy on "Making Indonesia 4.0", however, the current problem is the lack of contribution and the role of students in developing economic digitization. creative and marked by the lack of renewal of the Entrepreneurship course. Another problem is that there are still many agencies that have not been able to provide a website-based ecommerce container to accommodate student research results. With this problem, an ecommerce gamification-based student creative economy is utilized which aims to increase student interest in digitizing a creative economy and increase the number of quality scientific publications. Stages of research methods Gameplay e-commerce such as playing a game each user gets a level from the category of product purchased, of course, each level has its own features that make users interested in the privileges of each level.